Experimental Research: Design and Application - Intayos, Hutsayaporn; Seangdoung, Niphitphon (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
Experimental research is one of the forms of research that has been applied in various fields, such as science, social sciences, behavioral sciences, etc., including medical and public health research. Experimental research can be divided into three types: preliminary experimental research, quasi-experimental research, and true experimental research. This article will explain the meaning, required features, and research pattern of experimental research, including presenting research samples that apply experimental research. In order to be a body of knowledge for academics, researchers, and other interested parties to use as a knowledge base for further research applications.